Insights into diet and foraging behavior of imperial shags (Phalacrocorax atriceps) breeding at Staten and Becasses Islands, Tierra Del Fuego, Argentina - Harris, Sabrina; Saenz Samaniego, Ricardo Andres; Raya Rey, Andrea Nélida (The Wilson Journal of Ornithology)
Diet and behavior are essential aspects of ecological studies, and are even more informative if both aspects are studied together. We collected samples of feathers (n = 10 of unknown sex at Becasses Island in 2013) and of both feathers and blood at Staten Island (n = 5 males and n = 5 females in 2011 and in 2013) from Imperial shags (Phalacrocorax atriceps). In addition, GPS devices were deployed on two individuals at each location that allowed us to record one or two foraging trips each. Stable isotope composition of carbon and nitrogen in blood differed amongst years and between sexes, albeit marginally within each year at Staten Island. Feather stable isotopes of carbon and nitrogen did not differ amongst sexes or years at Staten Island and between Staten and Becasses islands to show individuals did not have significantly different diets amongst locations during pre-molt. Foraging behavior parameters did not differ between individuals as they all searched in shallow waters and close to shore. Individuals flew to their feeding grounds and searched intensively at the furthest point reached by diving interspersed with floating on the surface. These results show individuals feed on similar prey, at least during pre-molt, and would seem to behave in a similar way at both locations while breeding, though sample size is too small to generalize on their behavior. The differences in isotopic compositions amongst years for Staten Island could be showing the fluctuations that occur among seasons in the isotopic signatures of prey, and in consequence, in seabirds over time. Fil: Harris, Sabrina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Saenz Samaniego, Ricardo Andres. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Raya Rey, Andrea Nélida. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina